1993
DOI: 10.1007/bf00269138
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin E in follicle associated epithelium of intestine and tonsils: localization to M cells and possible role in antigen processing

Abstract: A specific rabbit anti-human serum was used selectively to localize the aspartic proteinase cathepsin E to follicle associated epithelium (FAE) of human and rat intestine, including jejunum, ileum, appendix, colon and rectum, as well as of human palatine, pharyngeal and lingual tonsils. Coexpression of class II histocompatibility antigen HLA-DR antigen has been observed in some of the cathepsin E-positive epithelial cells. In addition, cathepsin E has been detected in a few mononuclear cells of intestinal lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 31 publications
1
37
0
1
Order By: Relevance
“…A role of cathepsin E in antigen processing by professional or acquired immunocompetent cells (including epithelial cells such as intestinal M cells) has been suggested in the past [38,39], while more recently its expression has been found to be inducible by hematopoietic transcription factors and to be regulated by the HLA class II transactivator [40]. This function in cellular immune response, which fits with the highly enhanced expression of cathepsin E previously reported in H. pylori-infected gastric epithelium [41], may point to a role of this cathepsin in eliciting the antitumor T-cell response of HLR cancers.…”
Section: Discussionmentioning
confidence: 99%
“…A role of cathepsin E in antigen processing by professional or acquired immunocompetent cells (including epithelial cells such as intestinal M cells) has been suggested in the past [38,39], while more recently its expression has been found to be inducible by hematopoietic transcription factors and to be regulated by the HLA class II transactivator [40]. This function in cellular immune response, which fits with the highly enhanced expression of cathepsin E previously reported in H. pylori-infected gastric epithelium [41], may point to a role of this cathepsin in eliciting the antitumor T-cell response of HLR cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the non-follicular, cathepsin E positive cells in ileal and appendiceal epithelium is uncertain. However, Finzi and colleagues have described similar cells in the ileum and suggest they represent cup cells (Finzi et al 1993) which, like M cells, may be involved in the transportation of antigens and microbes across the intestinal epithelium (Madara et al 1985). The presence of cathepsin E in cells that handle antigen is in keeping with a potential role for the protease in antigen processing (Bennet et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Of these previous attempts to characterise a human M cell specific marker, the most promising involve sialyl Lewis A and cathepsin E, an aspartic proteinase potentially involved in antigen processing and presentation (Bennet et al 1992). However, in each case, the positive results have been presented in only one paper and have not been confirmed since (Finzi et al 1993, Giannasca et al 1999.…”
mentioning
confidence: 99%
“…Clusterin, fatty acid binding protein, cathepsin E, secretogranin V and other M-cell-expressed proteins may have potential roles in M cell functions, but these are less clearly understood. [56][57][58][59] The increasing evidences have demonstrated that M-cell-specific molecular antibody, which is conjugated with antigen protein or liver vector, can transport the antigen to mucosal tissues, leading to produce efficient immune responses. However, some molecules, selected as M-cell-specific molecules, are not uniquely expressed on M cells, resulting in producing a non-ideal oral delivery system for targeting M cells.…”
Section: Prpmentioning
confidence: 99%